Faktor-Faktor Yang Mempengaruhi Return Saham Perusahaan Perbankan Yang Telah Go Public Di Bursa Efek Indonesia - Anwar, Khabib; , Drs. Wiyadi, M.M., Ph.D (2017)
The purpose of this study was to analyze the effect of earning per share, dividend Payout Ratio, Net Profit Margin, Market Value Added, Free Cash Flow, Company Size. Based on the results of this study are expected to be considered by prospective investors as a reference in determining the right investments in the capital market, especially when investing in a manufacturing company. The data in this research is secondary data originating from banking companies that have gone public on the Indonesian Stock Exchange. Source data is based on ICMD (International Capital Market Directory). The research sample used is banking companies listed in Indonesia Stock Exchange 2010-2015 period. The analytical tool used to analyze the problems of the multiple linear regression analysis. Results from this study is the Earning Per Share positive and significant effect on stock returns, dividend Payout Ratio is not positive and significant effect on stock returns, Net Profit Margin positive and significant effect on stock returns, Market Value Added is not positive and significant effect on stock returns, Free Cash Flow positive and significant effect on stock returns, company size is not positive and significant effect on stock returns. The magnitude of the effect of the independent variable on the dependent variable at 93.0% while the remaining 7%isinfluencedbyothervariables.